3D Printing Technology and Its Application in Industrial Manufacturing. Issue 2 (March 2020) - Hao, Botao; Lin, Guomin
Abstract: 3D printing technology is widely used in industrial manufacturing, medical biology, and cultural creativity because of its direct molding.Based on the characteristics and advantages of 3D printing technology, this paper takes the 3D printing technology molding principle and process flow as the research object, and analyzes 3D Application of printing technology in automotive manufacturing, aerospace and electrical industries.